Psychological-Pedagogical and Methodological Peculiarities of Organizing the Teaching Process Based on the "4K" Model (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the psychological, pedagogical, and methodological features of organizing the teaching process based on the "4k" model, the advantages of the learning process based on the "4k" model, and the positive aspects of its practical implementation. At the new stage of society's development, attention is focused on the characteristics of improving the teaching system in primary education based on advanced foreign experiences, which is an important task facing this level of education.